Pengaruh Ukuran Perusahaan, Reputasi KAP dan Good Corporate Governance terhadap Ketepatan Waktu Penyampaian Laporan Keuangan - Sartika Riyanda; Efrizal Syofyan (Universitas Negeri Padang, 2021)
This study aims to determine the effect of firm size, reputation of public accounting firms, good corporate governance on non-financial companies listed on the Indonesia Stock Exchange. The population of this study is non-financial companies that have been late in submitting financial statements listed on the Indonesia Stock Exchange in 2017 – 2019. The sample is determined using the purposive sampling method as many as 24 companies. The results showed that the size of the company, the reputation of the public accounting firm and good corporate governance had no effect on the timeliness of submitting financial statements.